(untitled) (Pixel :Jurnal Ilmiah Komputer Grafis, 2025)
The high consumption of instant foods among elementary school children has become a significant concern due to its potential long-term health risks. This study aims to design interactive picture storybook characters as an educational medium for children aged 9–12 years to understand the dangers of instant foods and develop healthy eating habits. This study used a mixed-methods approach combined with design methodology, including a literature review, interviews with teachers, nutrition experts, and illustrators, and a questionnaire distributed to 114 respondents to identify children’s educational needs and visual preferences. The design process involved problem identification, concept development, prototyping, and validation through audience polling. This design features the main characters Lala, Lita, Ibu, and Perut Mascot, with brightly colored digital cartoon illustrations. The validation results showed that the characters and visual design align with the interests and needs of the target audience, making this medium effective in conveying educational messages in an engaging manner while motivating children to understand the risks of instant foods.